Combined On-Fault and Off-Fault Paleoseismic Evidence in the Postglacial Infill of the Inner-Alpine Lake Achensee (Austria, Eastern Alps) - Oswald, Patrick; Moernaut, Jasper; Fabbri, Stefano C.; De Batist, Marc; Hajdas, Irka; Ortner, Hugo; Titzler, Sebastian; Strasser, Michael (Frontiers in Earth Science, 2021)
The Eastern European Alps are characterized by slow active deformation with low- to moderate seismicity. Recurrence rates of severe earthquakes exceed the time span of historical documentation. Therefore, historical and instrumental earthquake records might be insufficient for seismic hazard assessment and high-quality paleoseismic data is required. However, primary geological observations of postglacial fault activity are scarcely found, because major faults are buried below thick sedimentary sequences in glacially overdeepened valleys. Moreover, high erosion rates, gravitational slope processes and penetrative anthropogenic landscape modification often obscure geomorphic features related to surface ruptures. Here we present one of the rare paleoseismic data sets showing both on-fault evidence as subaqueous surface ruptures and off-fault evidence as multiple coeval mass-transport deposits (MTDs) and megaturbidites within a single high-resolution seismic-stratigraphic framework of the inner-alpine lake Achensee. Co-occurrence of on-fault and off-fault paleoseismic evidence on three stratigraphic levels indicates seismic activity with inferred moment magnitudes MW ~6-6.5 of the local, lake-crossing Sulzgraben-Eben thrust at ~8.3 ka BP and twice in Late Glacial times. Additional eight stratigraphic levels with only off-fault paleoseismic evidence document strong seismic shaking related to the historical MW ~5.7 earthquake in Hall (CE 1670) and seven Holocene earthquakes, which have exceeded a local seismic intensity of ~VI at Achensee. Furthermore, we discuss natural and methodological influencing factors and potential pitfalls for the elaboration of a subaqueous paleoseismic record based on surface ruptures and multiple, coeval MTDs.